The clinical utility and validity of the cervical flexion-rotation test in the diagnosis and management of cervicogenic headache - Hall, Toby M (Curtin University, 2010)
Headache is a common complaint with increasing prevalence in the third decade. Because it is so common, headache gives rise to substantial financial costs to society. In addition headache burdens both the health care system and the family.Headache is a symptom arising from a range of different disorders. Consequently, classification of headache is important, as a successful outcome is only likely if intervention is targeted to the underlying cause. For example cervicogenic headache (CGH) appears to be uniquely amenable to physical intervention.Differential diagnosis of migraine and CGH is a common clinical challenge made difficult by symptom overlap and the presence of multiple headache forms (MHF). Consequently incorrect headache diagnosis is common. In individuals with headache symptom overlap, classification of CGH is based on physical examination. Cervical movement impairment is reported to be an important factor in CGH diagnosis. The flexion-rotation test (FRT) is an easily applied form of movement analysis, the aim of which is to identify C1/2 segment movement impairment.The general aim of this doctoral research was to analyze the clinical effectiveness of the FRT in CGH diagnosis. The FRT was evaluated in a series of six studies, which will be presented in sequence and grouped in Parts A, B, and C.Part A consisted of two studies. The first was designed to investigate the long-term stability and reliability of FRT measurements over time. Twenty-five subjects, 15 with CGH, were assessed using the FRT on 4 occasions spread over two-weeks. For subjects with CGH there was no significant change in FRT range of motion over days. Reliability was excellent and minimal detectable change was at most seven degrees.The second study in Part A was designed to investigate the diagnostic accuracy of the FRT. Sixty subjects with headache (20 with CGH, 20 with migraine and 20 with MHF) were evaluated using the FRT. The results demonstrate significantly greater deficits in range of motion in CGH. Based on the FRT, an experienced examiner was able to make the correct diagnosis of CGH 85% of the time. The cut-off value for a positive FRT was 30°.Part B consisted of two further studies designed to determine the validity of the FRT as a test of cervical movement impairment at, and pain arising from, the C1/2 segment. The aim of the first study was to measure rotation from the occiput to the C4 vertebra with the neck in neutral position and in flexion using Magnetic Resonance Imaging. Nineteen asymptomatic subjects were evaluated. There was a significant difference in the pattern of cervical segmental rotation between axial rotation and the FRT. At the C0/1 segment, there was negligible range recorded in either position. In contrast, the most mobile segment was C1/2, providing the majority of rotation during the FRT.The aim of the second study, in Part B, was to investigate the impact of lower cervical joint pain on the FRT. Twenty-four subjects were evaluated, 12 with CGH and 12 with lower cervical joint pain. A single examiner conducted the FRT. Subjects with lower cervical joint pain were evaluated using the FRT prior to therapeutic cervical spine block procedure and were excluded if they did not gain complete pain relief following that procedure. Range of rotation during the FRT was significantly less in the CGH group. Sensitivity and specificity for CGH diagnosis was 75% and 92% respectively. The cut-off value for a positive FRT was 32°.Part C consisted of two final studies designed to determine the clinical utility of the FRT in CGH evaluation. The aim of the first study was to investigate the reliability of manual examination and the frequency that segments above the C4 vertebra were the dominant source of symptoms in CGH. Eighty subjects were evaluated, 60 with CGH, and 20 who were asymptomatic. Two examiners evaluated each subject with standard manual examination procedures. Each examiner independently rated each segment for pain and dysfunction. The C1/2 segment was found to be the most commonly agreed dominant source of symptoms, with positive findings at this level in 63% of cases. Other segments were less frequently dominant.The aim of the second study in Part C, was to investigate the association between the presence and severity of CGH symptoms and the impairment in range of motion measured during the FRT. Ninety-two subjects were evaluated, 72 with CGH and an additional 20 asymptomatic subjects. A single experienced examiner conducted the FRT. Range of motion was significantly reduced by 6˚ in the presence of headache at the time of testing. Furthermore, half the variance in FRT range of motion was explained by an index of headache severity, or component parts.This series of studies has highlighted the central role that the FRT should play in the diagnosis of CGH. CGH principally arises from dysfunction of the C1/2 segment, although usually more than one segment is involved. Determining dysfunction at the C1/2 segment can be reliably achieved by using the FRT as well as manual examination procedures. The FRT, in contrast to manual examination, is an easily applied clinical test that is reliable, when used by experienced or inexperienced examiners. Measurement and interpretation of the FRT is stable over time. Range recorded during the FRT is related to the severity of headache symptoms. The presence of pain arising from segments other than C1/2 does not influence interpretation of the FRT. Finally, the similarity of headache characteristics but difference in cervical spine range of motion deficits (specifically the FRT) between those with migraine and those with CGH highlights the importance of the FRT in headache evaluation.